Down and Out. - Lezard, Nicholas (New Statesman, 2020)
I can't inflict that kind of writing on you and besides, that paragraph took me half an hour to write, and my editor is losing patience with me. First I was invited by the literary editor of the Chap magazine, because for some reason he thinks I am the bee's knees, to lunch at a very swanky restaurant just by Tower Bridge. As it happens I do not need to have touched a drop of liquor to promulgate the most outrageous stories about anyone, especially if they are about Toby Young, on whom I accumulated a lot of dirt and theories during the Nineties, when he was my editor at the Modern Review.